Analysis of the Motives and Risk Countermeasures for Cross-Border Mergers and Acquisitions of Agrochemical Companies Based on OLI Model: Taking the Case of China's Acquisition of Syngenta in Switzerland - Zhou, Jiake; Yuan, Canyang (International Journal of Global Economics and Management, 2024)
Nowadays, agrochemical companies are facing challenges such as fluctuations in supply and demand, intense market competition, and declining product prices, which have led to varying degrees of performance decline. At the same time, high-quality undervalued companies in the international market are attracting more and more Chinese companies to step into the global market in search of new growth opportunities through cross-border mergers and acquisitions. This paper, based on the OLI model, analyzes the motives of mergers and acquisitions from three aspects: ownership advantages, location advantages, and internalization advantages. It discusses the potential risks in the merger and acquisition process and preventive measures, and proposes relevant conclusions based on this.